Activity-based costing for competition against generic products: the case of an herbicide product company - Foong, Soon Yau; Ho, Beng Seng (Asia-Pacific Management Accounting Association, Accounting Research Institute & Faculty of Accountancy and UPENA, Universiti Teknologi MARA, 2009)
Activity-based costing (ABC) enables management to use activity cost information to formulate more effective strategy against competitors. Based on the case of herbicide product company, this paper examines how DCPM, a subsidiary of a multinational company, uses activity cost information to revise its pricing strategy to compete with the generic herbicide products, as the patent protection of its main herbicide product is coming to an end. The management of DCPM faces serious challenges of not only having to sustain its market share but also to achieve the profit target expected by its parent company. Using the activity cost information, DCPM is able to set competitive prices for different combinations of product and services to cater for customers with differing product/service price-sensitiveness. In the long term, however, the company would have to improve the overall cost efficiency in its product manufacturing and logistics services, as well as to educate users more extensively on the importance of quality and safety standards for herbicide products to sustain its market share.